1994
DOI: 10.1002/fut.3990140408
|View full text |Cite
|
Sign up to set email alerts
|

The informational content of USDA crop reports: Impacts on uncertainty and expectations in grain futures markets

Abstract: The current price of a futures contract conveys the expected price, as determined by the market, at the contract expiration date. However, futures prices do not indicate the degree of certainty that the market places on this price forecast. To obtain the market's certainty level about the price expectation, one must look at option prices. In fact, through option prices one can uncover the ex ante price probability distribution function.One factor which influences the shape or moments of the price distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…Implied volatility is a forwardlooking measure of volatility that reflects changes in expectations of market participants about future uncertainty. Several studies have shown that the arrival of new information alters the amount of uncertainty that market participants expect to be resolved before option expiration and results in significant changes in optionimplied volatility (e.g., Ederington & Lee, 1996;McKenzie et al, 2007;McNew & Espinosa, 1994;Patell & Wolfson, 1979). Around scheduled news events, resolution of uncertainty is characterized by a rise in implied volatility before the announcement date, a peak on the day before the announcement, and a fall to a new, lower level on the report day (for a hypothetical example, see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Implied volatility is a forwardlooking measure of volatility that reflects changes in expectations of market participants about future uncertainty. Several studies have shown that the arrival of new information alters the amount of uncertainty that market participants expect to be resolved before option expiration and results in significant changes in optionimplied volatility (e.g., Ederington & Lee, 1996;McKenzie et al, 2007;McNew & Espinosa, 1994;Patell & Wolfson, 1979). Around scheduled news events, resolution of uncertainty is characterized by a rise in implied volatility before the announcement date, a peak on the day before the announcement, and a fall to a new, lower level on the report day (for a hypothetical example, see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Donders and Vorst (1996) evaluate 96 scheduled corporate news disclosures and report that after a news release call option implied volatility 'drops sharply.' Examining the informational content of USDA crop reports for corn and soybeans, McNew and Espinosa (1994) observe similar changes in implied volatility for two agricultural markets. For both commodities, they observe an immediate 'drop' in implied volatility after the production estimates are announced.…”
Section: Literature Reviewmentioning
confidence: 78%
“…However, this traditional approach can result in inaccurate price estimates because the implied volatility is assumed to remain constant when trading is halted. Empirical research has shown that the arrival of new information alters the amount of uncertainty that investors expect to be resolved until option expiration and results in significant changes of the options implied volatility (Patell and Wolfson, 1979;McNew and Espinosa, 1994;Donders and Vorst, 1996;Ederington and Lee, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Garcia et al (1996) reason that traders perceive the USDA reports as containing less risk. McNew and Espinosa (1994) find reduced implied volatility in corn and soybean options after release of USDA crop forecasts. They observe that if market participants make their decisions on the basis of both risk and return, then any information which would reduce risk is valuable.…”
Section: Discussionmentioning
confidence: 99%